World malaria report 2018 - Muradi, Ahmad Mureed; Shoaib, Mohammad; Karima, Lammali; Guimaraes, Fernanda (Luxembourg : World Health Organization, 2018)
The wprld malaria report 2018 delivers a clearn message: the actions we take on malaria over the next 24 months will largely determine whether we can meet the 2025 milestones of WHO's global malaria strategy.
Contents Foreword Acknowledgements Abbreviations This year's report at a glance 1. Introduction 2. Investments in malaria programmes and research 3. Preventing malaria 4. Diagnostic testing and treatment 5. Malaria surveillance systems 6. Regional and global trends in burden of malaria 7. Malaria elimination and prevention of re-establishment 8. Responding to threats to the fight agains malaria 9. Conclusion References Annexes
Incluye Contenido
Incluye Referencias
Incluye Anexos
Keywords: PALUDISMO; MALARIA; ENFERMEDAD INFECCIOSA; FIEBRE AMARILLA; INFECCIONES POR PLASMODIUM ANOFELES; FIEBRE HEMOGLOBINURICA